Analisis Cultural Environment International Business Pada Perusahaan PT Unilever Indonesia - Antony Sentoso; Figo Winnerko; Andrian Andrian; William, Hardi Suandri, Delvian Yosuky, Vincent Linardo (STIE AMKOP, 2023)
This research aims to analyze the influence of the international cultural environment on the operational aspects of PT Unilever Indonesia's business. The phenomenon underlying this research is how PT Unilever Indonesia has successfully maintained good business performance amidst the diverse cultural differences in Indonesia. The research employs a qualitative method, utilizing literature reviews and interviews as primary data sources. The discussion covers the extent to which the local cultural environment influences the business strategy, organizational behavior, and leadership of PT Unilever Indonesia. The research findings indicate that PT Unilever Indonesia has been able to adjust its business strategy to accommodate the cultural differences present in Indonesia. Through a deep understanding of the local culture, the company has successfully integrated local values into its business strategy, formulated inclusive policies, and promoted diversity in the workplace. The conclusion of this research emphasizes the importance of understanding the cultural environment in managing international business and achieving long-term success in diverse markets such as Indonesia. Keywords: PT Unilever Indonesia, international cultural environment, business strategy, organizational behavior, leadership, cultural adaptation